ANALYSIS OF BUSINESS READINESS TO EXPORT FOR SMALL AND MEDIUM ENTERPRISE EMBROIDERY SECTOR IN KUDUS REGENCY - Selva Ulzana; Budi Prasetya; Luqman Khakim (Politeknik Negeri Semarang, 2015)
Embroidery in Kudus has a potential to export. Based on these, the purpose of this study was toidentify and analyze the readiness of SMEs Kudus embroidery to export their product. Themethods of collecting the data were questionnaire, Documentation, and Library Studies.Questionnaires were distributed to 45 SMEs embroidery sector as respondents. The studymethod uses multiple linier regression analysis.The multiple linier regression result shows that Y = 0.456 + 0.315X1171+ 0.216 X+0.904X4+ 0.193X5+ 0.082X. It means that result of regression gives a positive influence on theexport readiness. The coefficient of determination is 0.681 or 68.1%. It means that product,production, marketing, human resource, finance/export cost, and export procedure providepositive contribution to export readiness of 68.1% and 31.9% were influenced by others 6variables that were not examined in this study.Keyword: SMEs, Embroidery, Export Readiness